1994
DOI: 10.1073/pnas.91.20.9534
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a cDNA encoding an ectoenzyme that degrades thyrotropin-releasing hormone.

Abstract: Thyrotropin-releasing hormone (TRH) is an important extracellular signal substance that acts as a hypothalamic-releasing factor, which stimulates the release of adenohypophyseal hormones and functions as a neurotransmitter/neuromodulator in the central and peripheral nervous system. The Inactivation ofTRH after its release is catalyzed by an ectoenzyme localized preferentially on (14). The particulate peptidase is localized in synaptosomal (11) and adenohypophyseal (15) membrane fractions. In brain-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
72
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 47 publications
7
72
0
Order By: Relevance
“…Western blot analysis in reducing conditions showed that in transiently transfected COS-7 cells, wild type and mutated PPIIs were detected as a single band of 145 kDa, corresponding to the glycosylated PPII monomer (19). We observed very similar expression levels for Histagged wild type PPII and each of the eight mutated His-tagged PPII (Fig.…”
Section: Multiple Alignments and L-rap Modeling Suggest That In M1 Amsupporting
confidence: 48%
See 1 more Smart Citation
“…Western blot analysis in reducing conditions showed that in transiently transfected COS-7 cells, wild type and mutated PPIIs were detected as a single band of 145 kDa, corresponding to the glycosylated PPII monomer (19). We observed very similar expression levels for Histagged wild type PPII and each of the eight mutated His-tagged PPII (Fig.…”
Section: Multiple Alignments and L-rap Modeling Suggest That In M1 Amsupporting
confidence: 48%
“…The rapid inactivation of TRH by PPII in the central nervous system extracellular space (17,18) represents a significant drawback in its potential use as a therapeutic agent. Rat and human PPII cDNAs encode sequences with a high degree of conservation (19,20). Purification of the brain enzyme indicates that it is a glycoprotein composed of two identical subunits with a molecular mass of 230 kDa when solubilized with trypsin (21,22).…”
mentioning
confidence: 99%
“…: 353-1-608-1608; Fax: 353-1-677-2400; e-mail: kellyja@tcd.ie. 1 The abbreviations used are: TRH-DE, thyrotropin-releasing hormone-degrading ectoenzyme; TRH, thyrotropin-releasing hormone; Glp-His-ProNH 2 , L-pyroglutamyl-L-histidyl-L-prolineamide; Glp, pyroglutamic acid; CPHNA, N- [1-carboxy-2-phenylethyl]N-imidazole benzyl histidyl-␤-naphthylamide; TRHAMC, pyroglutamyl-histidyl-prolylamido-4-methyl coumarin; AMC, 7-amino-4-methyl coumarin; Fmoc, N-(9-fluorenyl)methyloxycarbonyl; tBu, t-butyl ether; Trt, triphenylmethyl; Pmc, 2,2,5,7,8-pentamethylchromane-6-sulfonyl; Boc, N-␣-t-butyloxycarbonyl; OtBu, t-butylester; HBTU, 2-(1H-benztriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate; HOBt, N-hydroxybenzotriazole; DIPEA, N,N-diisopropylethylamine; HPLC, high pressure liquid chromatography; DPP-IV, dipeptidyl peptidase IV; Thi, thienylalanine. All amino acids are in the L configuration unless otherwise stated.…”
mentioning
confidence: 99%
“…Thyrotropin-releasing hormone-degrading ectoenzyme (TRH-DE) 1 (EC 3.4.19.6) is a type II cell surface peptidase located on synaptosomal membranes in the central nervous system (1Ϫ4). TRH-DE catalyzes the hydrolysis of the Glp-His bond in thyrotropin-releasing hormone (TRH), a tripeptide with the amino acid sequence L-pyroglutamyl-L-histidyl-L-prolineamide (Glp-His-ProNH 2 ) (5Ϫ10).…”
mentioning
confidence: 99%
“…Gluzincin aminopeptidases share the consensus HEXXH(X) 18 E zinc-binding motif essential for enzymatic activity (10). This growing family of mammalian zinccontaining aminopeptidase includes membrane-bound (P-LAP, aminopeptidase A, aminopeptidase N, and thyrotropin-releasing hormone degrading enzyme) (3,4,6,11,12), cytosolic (puromycin-sensitive aminopeptidase (PSA) and leukotriene A 4 hydrolase) (13,14), secretory (aminopeptidase B) (15), and ER resident (A-LAP/ERAP1) (9,16) proteins. Mutational analyses revealed that essential amino acid residues are well conserved among members of the family (17)(18)(19)(20).…”
mentioning
confidence: 99%